Analysis of Students’ Mathematical Creative Thinking Skills through Problem-Based Learning on High School - Farida, Imas Siti; Hendriana, Heris; Supriatna, Tatang; Yuliani, Anik (IKIP Siliwangi, 2025)
The problem in learning mathematics today is how to develop creative thinking skills and make it a goal in the mathematics learning process, students often assume that mathematics can only be understood by some students. This research aims to descriptively analyze the creative thinking abilities of students whose learning uses the Problem-Based Learning model in Statistics material. This research uses a qualitative and descriptive-analytical approach by examining the data described to get a detailed and in-depth picture of students' mathematical creative thinking abilities in statistics material. The population in this study were all students at SMA Negeri 6 Tasikamalaya with a sample of 38 students in class X-9 at SMA Negeri 6 Tasikmalaya. In this research, it was found that the average student scores on questions number 1, 2, 3, and 4 were 8.81, 8.43, 7.47, and 9.62. From this analysis, students understand better the solution to question number 4 regarding problem number 4. Then the question that has the lowest average value is question number 3 which concerns the study of questions regarding searching for upper quartile and lower quartile data. So in future research, it is hoped that we will be able to analyze students' abilities in the form of their learning outcomes to see the influence, differences, and interactions that occur in students' mathematics learning outcomes based on their gender.